Transfers, non-traded goods, and unemployment : an analysis of the Keynes-Ohlin debate - Steven Brakman; Charles van Marrewijk (Center for Economic Studies and ifo Institute (CESifo), 2005)
In the famous debate between Keynes and Ohlin on the transfer problem, the interaction between non-traded goods and unemployment complicates the analysis considerably. We analyze these issues using four different models to conclude that Keynes's concern regarding the large burden imposed on Germany was justified. Simultaneously, we show that Ohlin's presumption that a transfer does not affect the donor's terms-of-trade either favourably or unfavourably was also justified. Moreover, Ohlin was also right in asserting that a transfer tends to lower the price of non-traded goods for the donor and raise them for the recipient.
Keywords: B0; O1; F0; 330; Internationaler Transfer; Terms of Trade; Nicht-handelbares Gut; Arbeitslosigkeit; Theorie; Deutschland <bis 1945>